Changing Sides - Bradley David Ridpath; Athena Yiamouyiannis; Heather Lawrence; Kristen Galles (University of Kansas Libraries, 2009)
The relationship of intercollegiate athletics and the federal Title IX statute has been the subject of significant concern and academic inquiry. This article explores the legal and legislative history of Title IX and the statute's impact on intercollegiate athletic programs and practical solutions for compliance. The article is broken into three distinct parts. Part I details a brief history of Title IX congressional, judicial, and regulatory involvement/enforcement over the past 36 years. Part II examines Title IX's application in practice with regard to public institutions and athletics. In Part III, the researchers present recommendations to wrestling programs and other men's teams concerning the economic realities of intercollegiate athletics. Specifically the researchers examine the wrestling community's legal and legislative challenges and explain how colleges' economic decisions and zeal for competitive teams at the "revenue sports" level are at the core of wrestling's dilemma rather than the law itself. The researchers also suggest more constructive solutions for preserving and expanding athletic opportunities for all without cutting men's sports programs. In particular, they argue that instead of attacking Title IX and women's sports, the wrestling community should form alliances with women's teams and their advocates to reverse the reallocation of resources in the college athletics arms race.